2021
DOI: 10.25259/ijdvl_1382_20
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of children with leprosy: Factors associated with delay in disease diagnosis

Abstract: Objectives: The objectives of the study were to characterize the clinical profile of childhood leprosy presenting at tertiary leprosy care hospitals in the states of Bihar, West Bengal and Uttar Pradesh in India, and to determine the possible risk factors associated with disabilities at presentation. Methods: Subjects were children with newly diagnosed leprosy registered for treatment at tertiary Leprosy Mission Hospitals in Muzaffarpur (Bihar), Purulia (West Bengal) and Faizabad (Uttar Pradesh), India, betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…In 2021, 7 children with leprosy were reported in China, one of whom was diagnosed with G2D disability, which indicates a delay in leprosy detection and late diagnosis. 22 As household contacts are the primary source of leprosy infection, leprosy prevention strategies must consider all people in contact with children, in addition to close relatives. [23][24] As the goal of 0 newly detected child cases with G2D in the Global Leprosy Strategy 2016-2020 was achieved in China in 2020, innovative tools for the early detection and diagnosis of leprosy in the next decade should be developed based on the present situation in China.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, 7 children with leprosy were reported in China, one of whom was diagnosed with G2D disability, which indicates a delay in leprosy detection and late diagnosis. 22 As household contacts are the primary source of leprosy infection, leprosy prevention strategies must consider all people in contact with children, in addition to close relatives. [23][24] As the goal of 0 newly detected child cases with G2D in the Global Leprosy Strategy 2016-2020 was achieved in China in 2020, innovative tools for the early detection and diagnosis of leprosy in the next decade should be developed based on the present situation in China.…”
Section: Discussionmentioning
confidence: 99%
“…Late diagnosis among children can be multifactorial, including the inability of health professionals to adequately detect the disease. In addition to this fact, a study conducted in tertiary hospitals in India observed that among the main risk factors associated with delayed diagnosis (represented by physical disability and/or positive bacilloscopy), socioeconomic vulnerability was a factor that increased the possibility of delayed diagnosis by 6 times ( 37 ). Socioeconomic aspects are deeply associated with the higher risk of development and progression of leprosy, and these factors can also be attributed to the high number of new cases found and the detection of physical disabilities in more than 30% of children diagnosed during this study ( 38 , 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many parents believed that the disease would go by itself, which is a serious concern as such delays often lead to excessive bacterial load and deformities in patients 48 . In some cases, access to a medical centre with proper diagnosis and treatment is also limited, which results in a prolonged delay 49 . These data also highlight the poor access to the healthcare system by STs, which could be the main reason that the expected level of leprosy control has remained elusive despite much-recognized achievements in other communities of the society.…”
Section: Scheduled Castes (Scs) and Scheduled Tribes (Sts)mentioning
confidence: 99%